Characterization of a bacterial strain T226 and its efficacy in controlling post-harvest citrus anthracnose - Wang, Qian; Song, Juan; Zeng, Quan; Ye, Xuelian; Shi, Guoying; Hu, Chunjin (Frontiers in Microbiology, 2025)
Postharvest anthracnose of citrus, caused by the fungus Colletotrichum gloeosporioides, leads to significant economic losses. There is a growing need for effective biological control agents to manage this disease. In this study, a bacterial strain (T226) with antagonistic potential was isolated from sugarcane rhizosphere soil. It was identified as Lysobacter enzymogenes through a polyphasic approach, encompassing 16S rDNA phylogenetic analysis (with 100% bootstrap support), morphological observation, and physiological and biochemical characterization. Strain T226 demonstrated strong and stable antagonistic activity against C. gloeosporioides. Its efficacy remained consistent over eight continuous subcultures on artificial media, indicating high metabolic stability. In vivo biocontrol assays confirmed its potency. Specifically, artificial stab inoculation tests showed a disease control efficacy of 78.2%, while under conditions of natural infection, T226 achieved control efficacies of 61.3% at 20 and 60 days post-application. To our knowledge, this is the first report identifying Lysobacter enzymogenes as a highly effective biocontrol agent against citrus postharvest anthracnose. The high stability and significant efficacy of strain T226 underscore its considerable potential for practical application in postharvest protection during citrus storage.